Electrodynamic braking in high‐speed rail transport - Liudvinavičius, Lionginas; Lingaitis, Leonas P. (Transport, 2007)
The paper considers electrodynamic braking of trains, which is of particular importance for high‐speed railway transport from theoretical and technical perspectives. Braking methods used for high‐speed trains should ensure compatibility and redundancy of braking systems. They include a mechanical method (based on adding frictional disks to wheelsets), as well as magnetic braking, which is being currently implemented and based on eddy currents, etc. High‐speed trains have AC/DC engines, for which the principles of electric braking can be applied. Electrodynamic braking is of particular importance for high‐speed transport using linear motors and developing the speed of 400–500 km/h. These traction rolling stocks will not have commonly used trucks. The tests in this area are being conducted in Japan and Germany now. The paper suggests some theoretical and practical solutions to these problems. Schematic diagrams of the locomotive braking and ways of controlling the braking force by varying electric circuit parameters are presented. The authors suggested contact‐free regulation of braking rheostat resistor for controlling braking force in rheostatic braking. A schematic diagram of harmonizing electrified railways and power system's upgrading aimed at ensuring power regeneration is also presented.First Published Online: 27 Oct 2010